Manajemen Ekstrakurikuler Paskibra dalam Membentuk Disiplin dan Tanggung Jawab Siswa - Anggun Nurma Dinda (BISMA : Business and Management Journal, 2025)
The formation of student character is an important aspect in the world of education, especially in instilling the values of discipline and responsibility. The Paskibra extracurricular at SMK Islam Al-Hikmah has a strategic role in building this character through various planned and systematic programs. This study uses a descriptive method with a qualitative approach, which uses data collection such as observation, interviews, and documentation. The results of the study First Planning, such as the formation of program plans, budget learning planning. Then the implementation, namely the time and program planning have been carried out well, there are facilities and infrastructure to support Paskibra extracurricular learning. Furthermore, evaluation to improve and enhance the Paskibra extracurricular. The advantages in this study are the formation of disciplined character, time management for students. While the shortcomings found are inadequate facilities and infrastructure, and technical matters of extracurricular activities.